Numerical analysis of hollow steel pile subjected to a combination of horizontal and vertical loads. (2022) - Baqi, Yusra; Khan, Junaid A.; Ahmad, Subhan; Sadique, M.R.
Abstract: This paper presents an analysis for investigating the nonlinear behaviour of a single hollow steel pile with a concrete pile cap subjected to different combinations of axial and lateral loads. The finite element based software ABAQUS/Explicit was used for the analysis. A number of load combinations were applied to understand the dynamic behaviour of hollow steel piles inserted in soil with different layers. Response of hollow steel pile in terms of vertical displacement, horizontal deflection and stresses developed in soil and pile was observed. The analysis results showed the pile's vertical downward settlement and horizontal deflection under different load combinations and the maximum amount of load the pile can carry before it fails. It further showed the stresses developed in the soil surrounding the pile.